1992
DOI: 10.2527/1992.7092682x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of crosses among Hereford, Angus, and Simmental cattle with different levels of Simmental breeding: VI. Maternal heterosis of 3- to 8-year-old dams and the dominance model2

Abstract: Data from Hereford, 25% Simmental-75% Hereford, 50% Simmental-50% Hereford, and 75% Simmental-25% Hereford dams were used to estimate maternal heterosis and level of agreement with the dominance model. Cows were located at the Northern Agricultural Research Center near Havre, MT and were managed consistent with practices for western range environments. Sample halves of dam breed groups were bred to Charolais and Tarentaise sires to produce calves at 3 to 8 yr of age. There were 766 exposures to breeding that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Similar to findings of Kress et al (1992), estimated heterosis was higher for Cow MY than that for Cow WG . The estimate of 5.5% observed in this study was within the range of 2.76 to 14.5% reported for beef cattle by Marshall et al (1976), Gregory et al (1992), and Kress et al (1992). Johnston et al (1995) reported an average 32% heterosis for Cow MY (Butson and Berg, 1984;Mezzadra et al, 1989;McCarter et al, 1991).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Similar to findings of Kress et al (1992), estimated heterosis was higher for Cow MY than that for Cow WG . The estimate of 5.5% observed in this study was within the range of 2.76 to 14.5% reported for beef cattle by Marshall et al (1976), Gregory et al (1992), and Kress et al (1992). Johnston et al (1995) reported an average 32% heterosis for Cow MY (Butson and Berg, 1984;Mezzadra et al, 1989;McCarter et al, 1991).…”
Section: Resultssupporting
confidence: 78%
“…Heterosis for Calf WG (8.0%) was higher than reported in the literature; Dillard et al (1980), Cundiff et al (1992), , and Kress et al (1995) noted estimates ranging from 3 to 5.8%. Heterosis for Cow WG , conversely, was to the low end of the range of 3 to 5.8% reported by Dillard et al (1980, and Kress et al (1992).…”
Section: Resultsmentioning
confidence: 75%
“…Corva et al (1995) reported a large estimate of weaning rate heterosis (0.1) for Criollo-Angus; no heterosis was detected for Romosinuano-Angus in the present study. Low estimates of heterosis for weaning rate in Bos taurus crosses were −0.03 (Gregory et al, 1978;Newman et al, 1993), but most were in the range from 0.03 to 0.07 (Cundiff et al, 1974;Peacock and Koger, 1980;Kress et al, 1992). Studies involving breeds with perhaps a greater milk role in their history (Brown Swiss, Milking Shorthorn) in combination with British breeds had a slightly higher range of estimates (0.09 to 0.13; Spelbring et al, 1977;Gregory et al, 1978;Olson et al, 1985).…”
Section: Calving and Weaning Ratementioning
confidence: 92%
“…Much as expected, the regression coefficients associated with direct and maternal heterozygosity did not differ significantly from zero (Table 4a,b). Under the hypothesis of dominance, which seems to be the case for growth traits in beef cattle (Kress et al, 1992;Gregory et al, 1994), heterozygosity has an effect opposite to that of inbreeding. Thus, the theoretical expectation is for heterosis to recover effects of inbreeding depression.…”
Section: Resultsmentioning
confidence: 99%